Fear of childbirth in time of the new coronavirus pandemic - Sandra Patrícia Arantes do Souto; Rosemeire Sartori de Albuquerque; Ana Paula Prata (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: Reflect on how the new coronavirus pandemic triggered or accentuated the fear of childbirth in pregnant women and affected childbirth care practices. Methods: Reflective analysis of women's pregnancy and childbirth experiences during the current pandemic, supported by the latest scientific evidence and recommendations on the topic. Results: Pregnancy and childbirth are life-changing events for women, but during the new coronavirus pandemic, fear and uncertainty have taken on an unprecedented dimension in the negative way that many pregnant women have anticipated and experienced childbirth. Final considerations: The current period has accentuated a chronic problem: a paternalistic system of health institutions in the approach to childbirth, dense with additional levels of fear in pregnant women. In this context, addressing the fear of childbirth means not giving up the promotion of safe and positive birth experiences for women.